2022
DOI: 10.1186/s12985-022-01786-2
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of lymphocyte subsets and cytokine profiles of patients with COVID-19

Abstract: Background Abnormalities of lymphocyte subsets and cytokine profiles have been observed in most patients with coronavirus disease (COVID-19). Here, we explore the role of lymphocyte subsets and cytokines on hospital admission in predicting the severity of COVID-19. Methods This study included 214 patients with COVID-19 who were treated at Chongqing University Three Gorges Hospital from January 19, 2020 to April 30, 2020. Any mutants were not detect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 30 publications
4
16
0
Order By: Relevance
“…It was shown, that selected parameters of immune profile (total number of lymphocytes, CD4 + , CD8 + , CD19 + ) might be used as predictors of severe COVID-19, with AUC values > 0,75 ( 34 , 74 ). In our study, none of examined parameters alone had sufficient sensitivity nor specificity to discriminate between survivors and non-survivors, the highest AUC values were obtained for lymphocyte and neutrophil counts and the total number of CD3 + , CD4 + and CD8 + cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown, that selected parameters of immune profile (total number of lymphocytes, CD4 + , CD8 + , CD19 + ) might be used as predictors of severe COVID-19, with AUC values > 0,75 ( 34 , 74 ). In our study, none of examined parameters alone had sufficient sensitivity nor specificity to discriminate between survivors and non-survivors, the highest AUC values were obtained for lymphocyte and neutrophil counts and the total number of CD3 + , CD4 + and CD8 + cells.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, none of examined parameters alone had sufficient sensitivity nor specificity to discriminate between survivors and non-survivors, the highest AUC values were obtained for lymphocyte and neutrophil counts and the total number of CD3 + , CD4 + and CD8 + cells. However, unlike other studies ( 34 , 74 ), we focused on discrimination between COVID-19 survivors and non-survivors, not severe and non-severe COVID-19 cases. As we have reported, patients with critical (group C) and fatal (group D) disease course did not differ significantly in most examined parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the cutoffs for lymphocyte subset absolute counts identified by our group (CD3+ < 524 cells/μL; CD3+CD4+ < 369 cells/μL; CD3+CD8+ < 194 cells/μL) [ 6 ] were similar to those described by other groups in different settings. Pan P et al found that a value of CD3+ T-cells < 510.5/µL and IL-6 > 6.58 pg/mL were predictors of progression to severe disease in a cohort of COVID-19 patients from China [ 26 ]. Belaid B et al analyzed PB lymphocyte subsets and cytokine levels in 57 COVID-19 patients from North Africa and, using multivariate logistic regression analysis and ROC curves, found that IL-6 > 106.44 pg/mL and CD8+ T-cells < 150/μL were predictive of increased mortality [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…22,23 Recent data have indicated that the high concentrations of IL-6 in COVID-19 patients due to cytokine storm was related to pulmonary in ammation, extensive lung damage, and even multiple organ failure. 22,24 Moreover, basic researches con rmed the increased serum levels of IL-6 may take part in the induction of lymphopenia through inducing apoptosis in T cells. 21,25 According to the ndings of the previous study, vaccine effectiveness was lower for the Omicron variant than for the delta variant, and the vaccine effectiveness reduced over time from 75.1% after 2 to 4 weeks to 14.9% after 25 or more weeks.…”
Section: Discussionmentioning
confidence: 99%